2007
DOI: 10.1002/bdrc.20090
|View full text |Cite
|
Sign up to set email alerts
|

The vertebrate segmentation clock and its role in skeletal birth defects

Abstract: The segmental structure of the vertebrate body plan is most evident in the axial skeleton. The regulated generation of somites, a process called somitogenesis, underlies the vertebrate body plan and is crucial for proper skeletal development. A genetic clock regulates this process, controlling the timing of somite development. Molecular evidence for the existence of the segmentation clock was first described in the expression of Notch signaling pathway members, several of which are expressed in a cyclic fashio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 104 publications
(126 reference statements)
0
24
0
1
Order By: Relevance
“…Several Notch signaling pathway components regulate somite segmentation, which underlies axial skeleton patterning (7). In addition, in vivo Notch pathway overexpression or underexpression in the osteogenic lineage demonstrates that Notch inhibits osteogenic differentiation and growth in the axial and appendicular skeleton (8)(9)(10).…”
mentioning
confidence: 99%
“…Several Notch signaling pathway components regulate somite segmentation, which underlies axial skeleton patterning (7). In addition, in vivo Notch pathway overexpression or underexpression in the osteogenic lineage demonstrates that Notch inhibits osteogenic differentiation and growth in the axial and appendicular skeleton (8)(9)(10).…”
mentioning
confidence: 99%
“…Furthermore, cyclic gene expression has been described in the presomitic mesoderm for many other genes linked to the Notch signaling pathway in mouse, zebrafish and chick (reviewed by Rida et al, 2004;Shifley and Cole, 2007). The Wnt pathway has also been linked to the clock.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in components of these signaling pathways have been linked to several malformations, including spondylocostal dysostosis (SCDO), Alagille sydrome (AGS), abnormal vertebral segments (hemivertebrae,wedge vertebrae, block vertebrae), spinal deformities, etc. [10,11] Recent findings have suggested that disruption of the retinoic acid (RA) pathway may lead to a loss of left-right bilateral symmetry in mouse embryos [12][13][14]. Thus, we hypothesize that RA signaling pathway may also play a role in the development of segmentation clock that regulates the segmental structure of the vertebrate body plan during embroyogenesis.…”
Section: Introductionmentioning
confidence: 99%